Analisis Yuridis Penegakan Tindak Pidana Narkotika Indonesia - Zahra, Latifa (UIR Law Review, 2023)
Based on the research results, it was revealed that law enforcement against narcotics crimes according to the Narcotics Law can result in imprisonment, fines, life imprisonment and other sanctions. In the context of protecting children involved in narcotics abuse, a victimology approach is used with a focus on rehabilitation, considering that children can be perpetrators and victims simultaneously. Meanwhile, the circulation of narcotics is analyzed from the perspective of international law, where prevention policies were initially regulated in The United Nation's Single Convention on Narcotic Drugs 1961. The problem of narcotics crimes has become an issue that continues to be discussed at the national and international levels. Narcotics abuse throughout the world is almost widespread and has the potential to cause negative impacts, such as physical damage, mental health, and emotional and behavioral disorders in society.